(untitled) (Experimental biology, 2015)
Actinomycetes are the significant component of microbiocenosis in the extreme ecosystems of the Northern Kazakhstan. The highest numbers of neutrophilic and halotolerant actinomycetes and their percentage component in the total biomass of bacteria are recorded in plant rhizosphere of sor and meadow saline soils. The richer qualitative composition of neutrophilic actinomycetes in rhizosphere of salt-tolerant plants, appearance of violet, red, blue and green pigmentary series of actinomycetes are also observed.